RNA polymerase III-mediated transcription of the trypanosome U2 small nuclear RNA gene is controlled by both intragenic and extragenic regulatory elements. - Fantoni, A (1994)
Transcription of U2 small nuclear RNA (snRNA) genes in eukaryotes is executed by RNA polymerase II and is dependent on extragenic cis-acting regulatory sequences which are not found in other genes. Here we have mapped promoter elements of the Trypanosoma brucei U2 snRNA gene by transient DNA expression of mutant constructs in insect form trypanosomes. Unlike other eukaryotic U2 snRNA genes, the T. brucei homolog is transcribed by an RNA polymerase III-like enzyme on the basis of its sensitivity to the inhibitors alpha-amanitin and tagetitoxin. Thus, the trypanosome U2 snRNA provides a unique example of an RNA polymerase III transcript carrying a trimethylated cap structure. The promoter of this gene consists of three distinct elements: an intragenic sequence close to the 5' end of the coding region, which is probably required to position the polymerase at the correct transcription start site; and two extragenic elements, located 110 and 160 nucleotides upstream, which are essential for U2 snRNA gene expression. These two elements closely resemble both in sequence and in distance from each other the A and B box consensus sequences of the internal control regions of tRNA genes.